تحسين خصائص الميكانيكية والعزل الكهربائى لطين الكاولين (University of Mosul-college of Basic Education, 2010)
في هذا البحث تم دراسة تأثير بعض المضافات مثل نشارة الخشب وأوكسيد الكالسيوم CaO والكوارتز وبنسب مختلفة في خاصيتي متانة الانضغاط والصلادة للكاولين المحلي المستخدم. بشكل عام ادت هذه المضافات الى زيادة متانة الانضغاط والصلادة .كذلك تم اجراء التحليل الكمي والنوعي للكاولين المحلي قبل وبعد معاملته بمحلول حامض HCl باستخدام تقنية XRF . ان معاملة الكاؤلين مع محلول حامض HCl ادى الى تقليل تراكيز كل من Fe2O3 والمعادن القلوية مما ادى الى تحسين خواص العزل الكهربائي للكاولين. This paper examines the influence of certain additives such as Sawdust ,CaO and quartz have been added with different proportions on Hardness and compression strength of the local kaolin .In general ,the additives used have increased the hardness and compression strength . The quantitative and qualitative analysis of the local kaolin before and after treatment with HCl acid solution was achieved using XRF technique . It has been found that the treatment of kaolin with HCl acid solution reduces the concentrations of Fe2O3 and alkali metals ,thus improving the dielectrical properties .